Smart Hospital Management System: Streamlining Healthcare Operations with SQL Integration - Gaikwad, Gaurav; Mahamuni, Chaitanya V; Kadam, Rohit; Pandita, Sunakshi (Journal of Trends in Computer Science and Smart Technology, 2024)
This research delves into the development and deployment of a Smart Hospital Management System (HMS), a pivotal solution for enhancing administrative efficiency and elevating patient care standards within healthcare institutions. Motivated by the pressing need to optimize hospital operations, the system seamlessly integrates modules encompassing patient registration, appointment scheduling, medical records management, billing, and inventory control. Leveraging modern technologies, particularly database management systems and web-based platforms, the HMS aims to bolster the efficiency, accuracy, and accessibility of healthcare services while prioritizing data security and regulatory compliance. The study scrutinizes the benefits and challenges associated with HMS adoption, shedding light on its potential impact on healthcare delivery and organizational performance. Furthermore, it underscores the contributions of this work to the research community, delineates future avenues for exploration, and offers insights into the promising prospects of smart healthcare systems.
Keywords: Smart Hospital Management System; Healthcare Operations; SQL Integration; Administrative Efficiency; Patient Care; Database Management Systems